Peningkatan Strategi Pemasaran Melalui Pelatihan Media Promosi Digital Pada Batik Tulis Moedjair Kandang Jaya Kabupaten Blitar - Wydha Mustika Maharani; Ferida Asih Wiludjeng; Indria Guntarayana (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The problem faced by partners is the low business capacity of the products sold. Meanwhile, the development of the business world is increasingly developing following the development of sophisticated technology, which requires business actors, especially batik craftsmen, not to be left behind. This is due to the product marketing system which is still conventional or the old tradition, namely through exhibition activities. The purpose of this service is to increase the business capacity of batik moedjair kandang jaya through an online marketing system. The solution offered by the proposer of this activity is to provide assistance in online product promotion and assistance in registering products in online applications so that it is expected to be able to increase business capacity and increase turnover or profits for batik craftsmen.